(untitled) (Modapalavra e-periódico, 2020)
When we face the study of dress from its artifactual identity, we observe that its so-called functional dimension cannot be understood in the same terms proposed by the ergonomics of the product, that is, from the ergonomic concepts of usability, efficiency, effectiveness and psychological comfort in relation to a specific activity or work. This article, presents the results of a review of the functional analysis methods commonly used by design for the study of clothing, and explains why they are insufficient or limited to address the multiple functions of this particular artifact. At the same time, it proposes some considerations for its functional analysis that contribute in a decisive way to the design process of the clothing design.